Acidified seawater increases accumulation of cobalt but not cesium in manila clam Ruditapes philippinarum. (April 2018) - Sezer, Narin; Kocaoğlan, Hasan Oğuz; Kılıç, Önder; Lacoue-Labarthe, Thomas; Belivermiş, Murat
Abstract: The pH of seawater around the world is expected to continue its decline in the near future in response to ocean acidification that is driven by heightened atmospheric CO2 emissions. Concomitantly, economically-important molluscs that live in coastal waters including estuaries and embayments, may be exposed to a wide assortment of contaminants, including trace metals and radionuclides. Seawater acidification may alter both the chemical speciation of select elements as well as the physiology of organisms, and may thus pose at risk to many shellfish species, including the manila clam Ruditapes philippinarum. The bioconcentration efficiency of two common radionuclides associated with the nuclear fuel cycle, 134 Cs and 57 Co, were investigated by exposing live clams to dissolved 134 Cs and 57 Co at control (pH = 8.1) and two lowered pH (pH = 7.8 and 7.5) levels using controlled aquaria. The uptake and depuration kinetics of the two radionuclides in the whole-body clam were followed for 21 and 35 days, respectively. At steady-state equilibrium, the concentration factor (CFss ) for 57 Co increased as the pH decreased (i.e. 130 ± 5, 194 ± 6, and 258 ± 10 at pH levels 8.1, 7.8 and 7.5, respectively), whereas the 134 Cs uptake was not influenced by a change in pH conditions. During depuration, the lowest depuration rate constant of 57 Co by the manila clam was observed at the intermediate pH of 7.8. An increase in the accumulation of 57 Co at the intermediate pH value was thought to be caused mainly by the aragonitic shell of the clam, as well as the low salinity and alkalinity of seawater used in the experiment. Considering that accumulation consists of uptake and depuration, among the three pH conditions moderately acidified seawater enhanced most the accumulation of 57 Co. Accumulation of 134 Cs was not strongly influenced by a reduced pH condition, as represented by an analogous uptake constant rate and CFss in each treatment. Such results suggest that future seawater pH values that are projected to be lower in the next decades, may pose a risk for calcium-bearing organisms such as shellfish. Highlights: Co accumulation in clam Ruditapes philippinarum might double due to ocean acidification. The highest CF of cobalt was observed in acidified seawater (pH:7.5). The longest Tb1/2 of cobalt was seen in moderately acidified seawater (pH:7.8). Cs uptake in clam Ruditapes philippinarum is not affected by increased p CO2 .